METHOD FOR PLANNING NON-DETERMINED OPERATION PROCESSES OF RAILWAY TECHNICAL SYSTEM PARK - Skalozub, V. V.; Klymenko, I. V. (Science and Transport Progress, 2018)
Purpose. The article is aimed to improve the automated systems operation of the railway technical system parks and switch D.C. electric motors (EMs), taking into account all uncertainties. Methodology. Solution of the problem was obtained through the development of the model and the method for optimal planning for the EMs set operation. The method is based on the information technology with the possibility to assess the parameters of the current and the predicted state of EMs based on their individual models. The models are built both for individual EMs and for the specified groups. The factors of non-determinism in the model are calculated based on the Hurst index. The task of planning is solved as calculating the optimal sequence of the EM facilities services, which provides a minimum of the total expected operating costs. Findings. The analysis of the main known models, the automated technologies and the systems of EM (ASEM) park operation on the basis of the remote monitoring was done in the research. Based on the practice of the EM park maintenance the new category of the analysis objects was proposed – the service group (SG). The new procedure for the processes classification was developed based on using the Hurst index to improve the reliability of EM and SG individual models forecasting. The technological and the economic model for planning the EM parks operation was created. The article presents the results of the developed automated data management system based on the improved model for the operation planning of the D.C. EM parks. The optimal planning model ensures the minimization of the expected operating costs for the EMs operation, due to the selection of the EM groups service queue. The specialized procedure is used to classify non-deterministic EM remote monitoring data during planning, which allows increasing the accuracy of forecasting the object state parameters. Origilnality. The article describes development of the mathematical model and the information technology for the remote monitoring of the railway technical systems park operation, the railway switch EMs based on the formation of EM and SG individual models, as well as on the evaluation of their current and predicted states, taking into account random factors. The proposed model of the optimal planning as the possibility to choose the SG service queue differs by the group maintenance of the EM facilities, as well as application of the specialized procedure for classifying EM monitoring data. Practical value. The practical value of the results is determined by the provision of the new opportunities for the group optimal planning of the EM service based on the criterion of the minimum expected costs. The procedure for the monitoring data classification of the operational processes makes it possible to increase the reliability of the forecasting antipersistent time sequences results. It also provides an interpretation of the observational data classification results based on the need for practical usage.